x+8=6-2x

Simple and best practice solution for x+8=6-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+8=6-2x equation:


Simplifying
x + 8 = 6 + -2x

Reorder the terms:
8 + x = 6 + -2x

Solving
8 + x = 6 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
8 + x + 2x = 6 + -2x + 2x

Combine like terms: x + 2x = 3x
8 + 3x = 6 + -2x + 2x

Combine like terms: -2x + 2x = 0
8 + 3x = 6 + 0
8 + 3x = 6

Add '-8' to each side of the equation.
8 + -8 + 3x = 6 + -8

Combine like terms: 8 + -8 = 0
0 + 3x = 6 + -8
3x = 6 + -8

Combine like terms: 6 + -8 = -2
3x = -2

Divide each side by '3'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| 3x-2y+3z=-4 | | (4n^3-4n)+(3n^3+7n+8)= | | 2x-y+z=-1 | | 17=-2*x+3 | | 3(7z-4)= | | 25k^2+30k+9=0 | | 125*5-25+10= | | (-3b^2-7b-4)+(7b^2+2b-4)= | | 4t+5+4t-7t=6+2 | | x^2(x^4+16)-8x=0 | | -5=5x^2-25x+25 | | log(6)(5x-3)=4 | | 25+2t=5(t+10) | | 8m+m=14+5m | | 7x+6x-4x=16+2 | | 2(m-3)=2(m-2.5) | | 30*50=x | | 30x*50=x | | 51-x=36 | | 14k(8-k+h)= | | 40c+120a=500 | | 5m-2=4+m | | -x-111+10x=33 | | -5x-6y-6x+7y= | | -5x-6y-6x+7= | | (7u^3-u^2-7)+(2u^3-4u^2)= | | 18x-8=-24 | | 0.80x=94 | | -3x^2+600x-3375=0 | | .50x+3+.80=1.80 | | 3b+1+b=2b+9 | | 3(y+2)=y+14 |

Equations solver categories